The Routledge handbook of ethnic conflict - Cordell, Karl; Wolff, Stefan (Oxon : Routledge, 2016)
"A definitive global survey of the interaction of ethnicity, nationalism and politics, this handbook blends rigorous theoretically grounded analysis with empirically rich illustrations to provide a state-of-the-art overview of the contemporary debates on one of the most pervasive international security challenges today. Fully updated for the second edition, the book includes a new section which offers detailed analyses of contemporary cases of conflict such as in Ukraine, Kosovo, the African Great Lakes region and in the Kurdish areas across the Middle East, thus providing accessible examples that bridge the gap between theory and practice. The contributors offer a 360-degree perspective on ethnic conflict: from the theoretical foundations of nationalism and ethnicity to the causes and consequences of ethnic conflict, and to the various strategies adopted in response to it. Without privileging any specific explanation of why ethnic conflict happens at a particular place and time or why attempts at preventing or settling it might fail or succeed, The Routledge Handbook of Ethnic Conflict enables readers to gain a better insight into such defining moments in post-Cold War international history as the disintegration of the Soviet Union and Yugoslavia, and their respective consequences, the genocide in Rwanda, and the relative success of conflict settlement efforts in Northern Ireland. By contributing to understanding the varied and multiple causes of ethnic conflicts and to learning from the successes and failures of their prevention and settlement, the Handbook makes a powerful case that ethnic conflicts are neither unavoidable nor unresolvable, but rather that they require careful analysis and thoughtful and measured responses."--
Keywords: Ethnic conflicts--Handbooks; Culture conflict--Handbooks